Classification of music based on correlation between mood, linguistic and audio features - Sobhan, Md. Mashrur Bari (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.